STUDY AND IMPROVEMENT OF STOCK CONTROL AVOIDING LOSSES AND DIVERGENCES IN A SUPERMARKET - Garbi, João Pedro Santos; Reis Filho, Ramilio Ramalho (Revista Interface Tecnológica, 2021)
Due to the competitiveness and competition present in the current market, for a company to remain within it, it is necessary to meet the needs of customers by investing in quality structure, services, products and employees, seeking methods to always be in a process of continuous improvement. The objective of this article is to study and improve the inventory control of a supermarket through quality tools such as check sheet, Pareto´s diagram, Ishikawa´s diagram and 5W2H. As a result, it was possible to propose an action plan with ideas for improvements to solve the causes of customer dissatisfaction and divergences in stock, which after being applied can cause an improvement in relation to excess, losses and shortages of goods, thus achieving customer satisfaction.
Keywords: quality; improvement; tools; stock; satisfaction